Specifics of Left Ventricular Remodeling and Daily Blood Pressure Profiles in Young and Middle-Aged Servicemembers Dealing with Arterial Hypertension - Botyrkhon Salikhov1, Bakhromkhon Alyavee1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objective: Investigating structural and geometrical parameters, specifics of LV remodeling, as well as dailyBP profiles in young and middle-aged service members dealing with hypertension Stage 1 and Stage 2. Agroup of 86 male subjects has been researched, including 52 young (26-44 y/o) and 34 middle-aged (45-55 y/o) subjects with AH. The cardiac function has been evaluated through echo cardiography, and dailyBP monitoring has been carried out. The results of the study have shown that young and middle-agedservicemen with AH have a normal LV geometry (59.6% of young subjects (31), 55.9% of middle-agedsubjects (19)), and concentric LV remodeling has been observed in 40.4% of young subjects (21) and in22.1% of middle-aged (15) subjects with AH. According to data obtained during 24-hr BPM,as comparedto the normal LV geometry group, in the concentric LV remodeling groups the occurrence of the dipper AHprofile has decreased both in young (28.5% vs. 39%) and middle-aged (40% vs. 47.7%) subjects.